ARTERIO-VENOUS (AV) FISTULA: SURGICAL OUTCOME AND PRIMARY FAILURE RATE - Iftikhar Ahmed; Mudassar Saeed Pansota (Journal of University Medical & Dental College, 2012)
ABSTRACT Objective: Outcome and primary failure rate of arteriovenous (AV) fistula at our setup. Data source: Patients admitted or referred to the Department of Urology with end stage renal disease and GFR≤30ml/min. Design of study: Prospective. Setting: Department of Urology and Renal Transplantation, Quaid-e-Azam Medical College/Bahawal Victoria Hospital, Bahawalpur. Period: From January 2010 to December 2011. Patients and methods: Fifty patients of age 16 to 65 years with ESRD and GFR ≤ 30ml/min, were included in the study. Allens test was performed on every patient and left upper limb was used for AV fistula formation. Preoperative sonographic vascular mapping was obtained in over 90% of cases. Side-to-end AV fistula was made under local anesthesia. Every patient was discharged on the 1st day after surgery. The follow up was performed on outpatient basis, every 7th day for 8 weeks, after which fistula was released to puncture for hemodialysis. Results: All patients had end stage renal disease with GFR ≤30 ml/min. Majority of the patients (58.0%) were between 16 to 35 years of age. Fifty five per cent were presented with etiology of diabetic or hypertensive nephropathy. Radiocephalic fistula was made in 40 (80.0%) while brachiocephalic fistula was made in 10 (20.0%) patients. The post-operative complications observed were hematoma 2.0%, thrombosis 4.0%, steal syndrome 4.0% and primary failure rate (within 2 weeks) was 6.0%. Overall complication rate was 16.0% with procedural success rate was 84.0% Conclusion: AV Fistula is the gold standard for vascular access for hemodialysis with an overall success rate of about 84.0%, and primary failure rate of 08%.